2012
DOI: 10.1007/s10048-012-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Systems genetic analysis of the effects of iron deficiency in mouse brain

Abstract: Iron regulation in the brain is both necessary and highly complex. Too little or too much iron can compromise neurological function, yet we still do not know all of the regulatory processes. In our research, we seek to identify genes and gene networks underlying individual differences in brain iron regulation. To this end, we fed mice from 20+ inbred strains a diet low in iron from weaning to 4 months of age. At sacrifice, we measured iron content in the ventral midbrain (VMB). The VMB contains the substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Glt-1 expression showed a strong negative correlation with VMB iron. 40 While this study did not measure protein, it could, nonetheless, indicate that iron deficiency occurs with increased glial uptake of Glu, consistent with the primary hypothesis of this project of increased glutamatergic activity in RLS.…”
Section: H Mrs)mentioning
confidence: 48%
“…Glt-1 expression showed a strong negative correlation with VMB iron. 40 While this study did not measure protein, it could, nonetheless, indicate that iron deficiency occurs with increased glial uptake of Glu, consistent with the primary hypothesis of this project of increased glutamatergic activity in RLS.…”
Section: H Mrs)mentioning
confidence: 48%
“…Iron is considered to be a risk factor in sPD per se , (Berg et al, 2001) and recently we showed that it co-operates with paraquat in neurotoxicity (Yin et al, 2011). This strain is also quite sensitive to disruption in iron regulation as a result of being fed an iron-poor diet (Jellen et al, 2012). That this strain is also among the most susceptible to MPTP toxicity and exactly how iron and MPTP toxicity in this strain are related remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…ID diet also produces peripheral organ (e.g., liver and spleen) iron deficiency and may also produce an anemia in some animals (Yin, et al, 2012), thus raising concerns as to the relevance of peripheral ID effects on the ID effects found in brain. Studies utilizing a broad range of BXD RI mice strains under normal and ID condition have not identified any significant relation between peripheral iron status and VMB iron status (Jellen, et al, 2012; Yin, et al, 2012). In cell culture models, where the issue of anemia or altered peripheral metabolism are not operational, changes in DAergic system with diminished iron concentrations were similar to DAergic system changes seen in ID animal (Connor, et al, 2009; Unger, et al, 2008; Wiesinger, et al, 2007).…”
Section: Discussionmentioning
confidence: 98%